KEBERHASILAN PERTAUTAN SAMBUNG PUCUK PADA MANGGA DENGAN WAKTU PENYAMBUNGAN DAN PANJANG ENTRIS BERBEDA - Yohanis Tambing; Abd. Hadid (Universitas Tadulako, 2008)
The objective of the research was to identify scion length and time for a successful graft union of mango plant. The experiment used a Randomized Block Design with factorial pattern replicated three times. The factors consisted of grafting time (morning, noon, and afternoon), and scion lengths (7.5, 10 and 12.5 cm). The research results showed that grafting in the afternoon produces better graft union seedling. However, grafting conducted at noon could also generate good graft union seedling as long as the length of the scion was 12.5 cm. The results from the research was still far from perfect. Therefore, it is recommended that the research should be continued in order to identify the treatment consistency.